Legal Protection for Minors as Victims of Online Prostitution from the Perspective of Law Number 35 of 2014 on Amendments to Law Number 23 of 2002 on Child Protection - Gultom, Samuel; Hutapea, Novelina Mutiara S; Damanik, Jenriswandi (Pancasila and Civics Education Journal (PCEJ), 2025)
ABSTRACTOnline prostitution of minors is an act that aims to obtain and can also be offered a child's sexual services by someone or to another person and is accompanied by a payment in the form of money. Online prostitution is an exchange of sexual relations with a reward that is usually in the form of money as a trade or prostitution transaction carried out through the internet or cyberspace as a connecting medium. The media used such as, whatsapp, messenger, facebook, line, and so on. The purpose of this study is to explain the legal protection of minors as victims of online prostitution, the form of legal protection for minors as victims of online prostitution, and efforts to prevent and handle online prostitution. To obtain the data needed in this study, normative legal research was conducted. Normative legal research produces primary data, namely legal materials consisting of laws and regulations, such as Law Number 35 of 2014 Amendment to Law Number 23 of 2002 Concerning Child Protection. And produces secondary data, namely studying books, theories and scientific papers. The results of the study indicate that how legal protection for minors as victims of online prostitution and efforts to prevent and handle online prostitution. However, the form of legal protection requires firmness from Law Number 35 of 2014 Amendment to Law Number 23 of 2002 Concerning Child Protection. In providing protection, so that with strict regulations, minors can be protected by law. Efforts to prevent and handle online prostitution can be seen in terms of prevention before it occurs and handling after a crime occurs. It is recommended that law enforcement officers be able to carry out improvements in institutions by always increasing the professionalism and quality of investigators, also strengthening legal regulations or prohibiting online media for any publications that lead to pornographyKeywords: Child Protection Law Enforcement, Legal Protection of Minors, OnlineProstitution Prevention